Effect of Immobilization Method on the Growth of Chlorella vulgaris and Fatty Acid Profile for Biodiesel Production - Nur Hanani Rushan; Nur Hidayah Mat Yasin; Noor Raihana Abu Sepian; Farhan Mohd Said; Nurafifah Izzati Shafei (Indonesian Journal of Chemistry, 2019)
The aim of this research is to study the immobilization effect on growth cell of microalgae Chlorella vulgaris. The comparison of lipid production between immobilized microalgae and free cell culture was also studied and the fatty acid methyl ester for biodiesel production was identified in this research. Four important steps were done in this research which included microalgae cultivation, harvesting method by immobilization, lipid extraction and transesterification of oil. In the immobilization method, the combination of matrix system of sodium alginate and sodium carboxymethylcellulose (SA and CMC) gave the highest number of cells of microalgae after the 9th day of the cultivation process. However, the immobilized microalgae matrix system of SA at volumetric ratio of 0.3:1 showed better results for extraction of oil, attaining an oil yield percentage of 46% compared with other matrix systems studied; SA + CA + CMC (43.00%), SA + CA (41.19%), SA + CMC (40.38%) and free cell culture (42.57%). Furthermore, the fatty acids methyl ester profile of the extracted oil showed high potential for biodiesel production. The results proved that the immobilization of microalgae had improved the oil yield and fatty acid composition as compared to the free cell culture, which may have useful application for the biofuel industry.